2014
DOI: 10.3402/jchimp.v4.23084
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic detection of occult indeterminate pulmonary nodules using bronchoscopic pleural dye marking

Abstract: BackgroundThe annual incidence of a small indeterminate pulmonary nodule (IPN) on computed tomography (CT) scan remains high. While traditional paradigms exist, the integration of new technologies into these diagnostic and treatment algorithms can result in alternative, potentially more efficient methods of managing these findings.MethodsWe report on an alternative diagnostic and therapeutic strategy for the management of an IPN. This approach combines electromagnetic navigational bronchoscopy (ENB) with an up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 19 publications
0
71
1
Order By: Relevance
“…The sole use of methylene blue, India ink, lipiodol and barium have also be reported in a few small series (48)(49)(50)(51)(52). Similar to the microcoil technique described above, most series involve the percutaneous placement of the contrast material yet some recent reports are using bronchoscopic guidance for pleural dye marking (53,54). Although a potentially promising technique, success rates as low as 81% have been reported due to both diffusion of the dye in the pleural space and lack of visualization of the dye (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sole use of methylene blue, India ink, lipiodol and barium have also be reported in a few small series (48)(49)(50)(51)(52). Similar to the microcoil technique described above, most series involve the percutaneous placement of the contrast material yet some recent reports are using bronchoscopic guidance for pleural dye marking (53,54). Although a potentially promising technique, success rates as low as 81% have been reported due to both diffusion of the dye in the pleural space and lack of visualization of the dye (53).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the microcoil technique described above, most series involve the percutaneous placement of the contrast material yet some recent reports are using bronchoscopic guidance for pleural dye marking (53,54). Although a potentially promising technique, success rates as low as 81% have been reported due to both diffusion of the dye in the pleural space and lack of visualization of the dye (53). This technique has also been used in children, with one series reporting lung tattooing and VATS resection during the same general anaesthetic (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Total procedure time including NB-guided peritumoral injection was similar to previous reports adding on average 20 minutes to the operative time for both diagnosis, when indicated, and labeling of the lesions 29 . Importantly, other approaches to intraoperative detection of pulmonary nodules have been described, including lesion localization with blue dyes, microcoils, percutaneous wire placement and intravenous ICG, but none of these techniques permit concurrent SLN mapping for the lesion of interest 3035 .…”
Section: Discussionmentioning
confidence: 99%
“…Electromagnetic navigational bronchoscopy uses sensor-location technology in concert with a 3D reconstruction of CT scan data in order to guide a bronchoscopic probe to a lung nodule. 11,12 This yields a virtual bronchoscopic reconstruction that can be paired with true bronchoscopic images to facilitate injection of dye or fiducial. The few reported human studies on this topic are small case series.…”
Section: Localization Of Small Pulmonary Nodulesmentioning
confidence: 99%
“…11 Bolton et al reported 100% localization in 11 patients using methylene blue dye via electromagnetic navigational bronchoscopy followed by robotic wedge resection. 12 Both studies reported no need for conversion to open resection or adverse events related to the marking procedure.…”
Section: Localization Of Small Pulmonary Nodulesmentioning
confidence: 99%